The influence of product quality and restaurant environment towards customer return in specialty restaurant / Farah Amalina Ibrahim - Ibrahim, Farah Amalina (2013)
The foodservice industry is one of the fastest growing industry and continually develop in the future. As a restaurant service provider, it is important to retain the current customer and to recruit new one in order to sustain the restaurant business. The purpose of this study is to examine the influence of product quality and restaurant environment towards customer return in specialty restaurant. Customer return is often indicated by customer’s satisfaction. Hence, to ensure that the customer will return and spread the positive word-of-mouth, it is important to satisfy the customer. This study was conducted with causal research design and quantitative methods were used to measure the variables. A structured questionnaire was used as the data collection method. Nonprobability sampling method with five points Likert scale was used to measure the customer response. The population study includes customer of specialty restaurant which were randomly chosen around Shah Alam. Approximately, 400 questionnaires were distributed to engage customer’s responses. Descriptive analysis, multiple regressions and mediating analysis were used to analyze the data. The findings showed that the product quality (β = 0.384, p < 0.05) and restaurant environment (β = 0.342, p < 0.05) has significant influence towards customer return and customer satisfaction mediate the relationship (with 95% bias corrected and accelerated confident interval excluding zero 0.127 to 0.299 and 0.188 to 0.327). Offering high quality products with delightful environment will not only increase satisfaction and return intention, but also improve the business reputation and generate better revenue.